Listening to Australian Indigenous men: stories of incarceration and hope. Issue 6 (12th August 2016) - Macdonald, John; Scholes, Tony; Powell, Kay
Abstract : Objective: This paper reports on a project conducted between 2008 and 2011 that was established to allow eight Australian Indigenous men who had been in prison to tell their stories of incarceration. Background: The Shed in Western Sydney, NSW, Australia, was set up in response to the high male suicide rate in that area, its objective being to support men at risk. Aboriginal men were the most at risk, and they are presently imprisoned at a rate of 13 times more than non-Indigenous men. This small project sought to give voice to the men behind the statistics and point to a significant problem in Australian society. Methods: Interviews were conducted by an Indigenous male, questions covering age at first entering the penal system, number of prison stays, support, and health. This paper is framed around responses to these questions. Results: All but one of the men were recidivist offenders, and over half were under 15 years of age when first offending. All talked about a lack of support both inside and after leaving prison, and alcohol and depression figured strongly in the accounts. Disadvantage and social exclusion, lack of support such as access to housing and health services, figure significantly in the men's stories. It is only when social issues are addressed that any gains will be achieved and a cycle of recidivism broken.